1996
DOI: 10.1016/0005-2736(96)00009-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical pressures in multicomponent lipid monolayers

Abstract: Epifluorescence microscopy has been used previously to study coexisting liquid phases in lipid monolayers of dihydrocholesterol and dimyristoylphosphatidylcholine at the air/water interface. This binary mixture has a critical point at room temperature (22 degrees C), a monolayer pressure of approx. 10 mN/m, and a composition in the vicinity of 20-30 mol% dihydrocholesterol. It is reported here that this critical pressure can be lowered, raised, or maintained constant by systematically replacing molecules of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
16
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
6
16
0
Order By: Relevance
“…Previous work has reported that the miscibility transition pressure of monolayers containing phospholipid and 20 mol% Dchol is linearly, systematically altered by the addition of a second phospholipid (Hagen and McConnell, 1996). This conclusion is true for the cases previously studied.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Previous work has reported that the miscibility transition pressure of monolayers containing phospholipid and 20 mol% Dchol is linearly, systematically altered by the addition of a second phospholipid (Hagen and McConnell, 1996). This conclusion is true for the cases previously studied.…”
Section: Discussionsupporting
confidence: 69%
“…4). The phase diagram for this mixture does not differ significantly from the shape of common binary phase diagrams of phospholipid and Dchol (Hagen and McConnell, 1996;Keller et al, 2000). At transition points far from the critical point, stripes are not seen (open symbols, Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Mixtures of phospholipids alone have not generally been found to exhibit liquid-liquid immiscibility in monolayers. However, immiscibility is seen in binary mixtures of cholesterol with the phospholipids phosphatidylcholine [1][2][3][4], phosphatidylethanolamine [10], or phosphatidylserine [11]. Cholesterol and egg sphingomyelin also exhibit immiscibility (data not shown).…”
mentioning
confidence: 99%
“…At the putative critical composition, the pressure is changed until the critical pressure p c is found. Conducting experiments at physiological temperature (37 ± C) rather than room temperature (23 ± C) is expected to lower the critical pressure by only 1-3 dyn͞cm, assuming the average values of the a ij are similar [10,14]. Figure 3(a) gives a schematic ternary phase diagram for two ideally mixing phospholipids (components 1 and 2) and cholesterol (component 3).…”
mentioning
confidence: 99%